The Bank of Canada's "horse race" of alternative monetary policy frameworks: Some interim results from model simulations - José Dorich; Rhys Mendes; Yang Zhang (Bank of Canada, 2021)
Since 1991, the Bank of Canada has had an inflation-targeting (IT) framework established by a joint agreement between the Bank and the Government of Canada. The framework is reviewed every five years as part of the process for renewing the inflation-control agreement. This discussion paper summarizes some interim results from Bank staff analysis done for the August 2020 workshop, "Towards the 2021 Renewal of the Bank of Canada's Monetary Policy Framework." The Bank will publish updated analysis later in 2021. The core of the current framework-the 2 percent inflation target-has remained unchanged since 1995. This fact reflects its success. Well-anchored inflation expectations contribute to macroeconomic stability while leaving monetary policy with greater flexibility. The 2021 renewal highlights two key challenges facing Canadian monetary policy: (1) the low neutral rate of interest; and (2) the low interest rates associated with a low neutral rate that may encourage excessive risk taking and debt accumulation To address these challenges, Bank staff are running a "horse race" of alternative monetary policy frameworks (i.e., alternatives to the 2 percent IT framework). Their work evaluates these alternatives using a broad range of qualitative and quantitative criteria and focuses on the macroeconomic performance of the alternative frameworks. The interim results we report in this discussion paper suggest overall that no framework dominates on all margins. As a result, the ranking depends on the relative weight placed on different criteria.
Keywords: E; E2; E27; E3; E4; E5; E52; E58; 330; Central bank research; Economic models; Inflation targets; Monetary policy framework; Monetary policy; Monetary policy transmission